Pemanfaatan Liveworksheet sebagai E-LKPD dalam Meningkatkan Hasil Belajar PAI Tingkat Sekolah Dasar - Wangi, Arisa Natasha (ALSYS, 2024)
There are significant differences in the implementation of the independent curriculum between urban and rural areas, especially in 3T areas. These differences start with teacher performance and extend to all aspects of education, including learning administration, teaching methods, and the way teachers assess, especially based on student learning outcomes. The aim of this research is to determine the use of live worksheets as E-LKPD in improving PAI learning outcomes at the elementary school level. This exploration uses a quantitative methodology with a pre-experimental configuration using a One Gathering Pretest-Posttest design. Based on the results of data analysis and questionnaires, the average student response to the use of live worksheets as E-LKPD in improving PAI learning outcomes was 79% in the practical category. Apart from that, the Paired Sample T-Test shows differences in PAI subjects before and after using E-LKPD, with an average score of 64.63 percent which is in the quite effective category and the significance level is below 0.05 or 0.001.